Wesselsbron virus : a biophysical, biochemical and serological study - Parker, Joan Rae (Division of Medical Virology, 2020)
The application of variety of virological techniques to the study of Wesselsbron virus hos resulted in the compiling of much worthwhile information on the biophysical, biochemical and serological properties of this virus. Wesselsbron virus , like most arboviruses, showed marked sensitivity to the action of bother ether and sodium deoxycholate.